Angola : Fourth Review Under the Extended Arrangement Under the Extended Fund Facility and Requests for Modifications of Performance Criteria and Waivers for Performance Criteria Applicability and Nonobservance-Press Release; Staff Report; and Statement by the Executive Director for Angola. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2021)
While improving, the economic outlook remains highly challenging, given the slow and uncertain recovery from the COVID-related shocks. Heavily dependent on oil, the Angolan economy has suffered from weakness in that sector, with falling production (related to the pandemic) and only a partial rebound in international prices recently. These shocks have led to a fifth straight year of recession and hardship. The public debt-to-GDP ratio has risen to very elevated levels, driven by recent real exchange rate depreciation. Nevertheless, strong fiscal performance and active debt management are setting the stage for a gradual economic recovery and reduction in debt vulnerabilities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet